2022
DOI: 10.1177/02610183221104976
|View full text |Cite
|
Sign up to set email alerts
|

The banality of state violence: Institutional neglect in austere local authorities

Abstract: Theorisations of state violence under austerity have been criticised for their imprecision. In response, this article introduces the concept of institutional neglect: a specific modality of structural violence. We argue that institutional neglect occurs when state services deny care to eligible clients. This is a normative claim which locates an obligation to care in the body of the state. Through case studies of two local authority-run care services in the UK, we identify three banal, quotidian techniques of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…School food banks and food pantries are emblematic of schools acting as crucial anchor institutions in the face of a retreating welfare state and the underfunding of services that should provide a supportive ecology for families, communities and child development (Kiely & Warnock, 2022). A pattern that emerged from the data was that schools felt compelled to take responsibility for ameliorating the effects of broader social problems by, in effect, providing ‘crisis’, ‘emergency’ and ‘universal’ services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School food banks and food pantries are emblematic of schools acting as crucial anchor institutions in the face of a retreating welfare state and the underfunding of services that should provide a supportive ecology for families, communities and child development (Kiely & Warnock, 2022). A pattern that emerged from the data was that schools felt compelled to take responsibility for ameliorating the effects of broader social problems by, in effect, providing ‘crisis’, ‘emergency’ and ‘universal’ services.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that schools are increasingly providing necessities to children in the form of food, clothing, shoes and cleaning products (NASUWT, 2022). This can also be traced to longer term cuts in local and central government budgets, which have led to the scaling back of child and family support services—from children's centres to social care, youth work and crucial mental health services—and amount to state‐orchestrated ‘institutional neglect’ (Hanley et al., 2020; Kiely & Warnock, 2022). Geoff Barton, the General Secretary of the Association of Schools and College Leaders, has concluded that ‘A decade of austerity has wreaked havoc with the social fabric of the nation and schools have been left to pick up the pieces while coping with real‐term funding cuts’.…”
Section: Definitions and Contextmentioning
confidence: 99%
“…A growing scholarship documents the violence of the UK welfare system, and especially of ‘welfare reform’. Austerity driven post-2010 UK welfare reforms have been conceptualised as violence that is ‘cruel, inhuman and degrading’ (Adler, 2018, title page); ‘institutional’ ‘ordinary’, ‘mundane’ (Cooper and Whyte, 2017:23); ‘bureaucratised’ (Redman and Fletcher, 2022); and banal (Kiely and Warnock, 2023). More than an unfortunate policy side-effect, fear is directly and indirectly designed into social security, constituting what some see as a ‘war on welfare’ (WOW Campaign) and a ‘war on disabled people’ (Clifford, 2020).…”
Section: Welfare Violencementioning
confidence: 99%
“…Emerging evidence suggests that schools are increasingly providing necessities to children in the form of food, clothing, shoes, and cleaning products (NASUWT 2022). This can also be traced to local and central government budget cuts that has led to the scaling back of child and family support services -from children's centres, social care, youth work, and crucial mental health services -and amounts to state orchestrated 'institutional neglect' (Hanley et al 2020;Kiely and Warnock 2022). Geoff Barton, the general secretary of the Association of Schools and College Leaders has concluded that, 'A decade of austerity has wreaked havoc with the social fabric of the nation and schools have been left to pick up the pieces while coping with real-term funding cuts.'…”
Section: Developing a Theory Of Food Charity In Schoolsmentioning
confidence: 99%